2019
DOI: 10.1111/jopr.13088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment and Cement on Fracture Load of Traditional Zirconia (3Y), Translucent Zirconia (5Y), and Lithium Disilicate Crowns

Abstract: Purpose To determine if surface treatment and cement selection for traditional 3 mol% yttria partially stabilized zirconia (3Y‐PSZ), “translucent” 5 mol% yttria‐stabilized zirconia (5Y‐Z), or lithium disilicate crowns affected their fracture load. Materials and Methods Crowns with 0.8 mm uniform thickness (96, n = 8/group) were milled of 3Y‐PSZ (Lava Plus), 5Y‐Z (Lava Esthetic), or lithium disilicate (e.max CAD) and sintered/crystallized. Half the crowns were either particle‐abraded with 30 µm alumina (zirconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 21 publications
2
52
1
2
Order By: Relevance
“…Like other studies such as Camposilvan and Lawson, the present trial found significant differences between tetragonal monolithic zirconia (Group TMZ) and cubic monolithic zirconia (Group CMZ), with higher fracture resistance obtained in Group TMZ [12,13].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Like other studies such as Camposilvan and Lawson, the present trial found significant differences between tetragonal monolithic zirconia (Group TMZ) and cubic monolithic zirconia (Group CMZ), with higher fracture resistance obtained in Group TMZ [12,13].…”
Section: Discussionsupporting
confidence: 76%
“…Monolithic zirconia crowns may be stabilized in tetragonal phase, when they present a strength equal to metal-ceramic crowns but with the disadvantage of high opacity [2,3,4,8]. For this reason, zirconia crowns stabilized in cubic phase have been introduced, which offer greater translucency and so better aesthetics, but less strength and hardness [12,13]. Camposilvan analyzed the hardness of zirconia stabilized with different proportions of cubic structure and found that as the percentage of cubic zirconia increased so did its translucency, while strength and hardness decreased [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the conditions of the studies should be established since they can influence the results. Some studies used resin dies because their elasticity modulus is similar to dentin [ 37 , 41 ], while others used metallic dies, as in the present study [ 1 , 6 , 8 , 13 , 22 , 25 , 38 , 42 ], which provide for the standardization of the shape and dimensions of the specimens [ 6 , 42 ], and also avoid possible premature destruction when testing metallic alloys compared to natural or resin teeth [ 43 , 44 ]. In the study, real frameworks were used instead of bar-shaped, cylinder, or disc specimens [ 29 , 45 ], and the thickness was also standardized to simulate clinical conditions [ 37 , 44 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%